Exosomal ncRNAs: The pivotal players in diabetic wound healing - Shen, Jiuheng; Zhao, Xian; Zhong, Youxiu; Yang, Peng; Gao, Peifen; Wu, Xue; Wang, Xudong; An, Wenlin (Frontiers in Immunology, 2022)
Diabetes is the most prevalent metabolic disease in the world today. In addition to elevated blood glucose, it also causes complications that significantly interfere with life quality of patients. Diabetic trauma is a complication as a result of the interaction of diabetic neuropathy, peripheral vascular disease, infection, trauma and other factors, which usually leads to poor healing of the trauma and even to severe foot ulcers, wound gangrene and even amputation, causing serious psychological, physical and financial burdens to diabetic patients. Non-coding RNAs (ncRNAs) carried by exosomes have been demonstrated to be relevant to the development and treatment of diabetes and its complications. Exosomal ncRNA not only provides a novel strategy to the clinical diagnosis of diabetes, but also a new direction to cure people with diabetes. It has been widely reported that ncRNAs in exosomes can promote diabetic wound healing by regulating inflammation, accelerating re-vascularization, re-epithelialization as well as extracellular matrix remodeling. This article reviews recent research advances to close up diabetic wound and discusses the challenges and perspectives of exosomes in term of ncRNA themselves or as delivery vehicles to accelerate diabetic wounds healing, with the aim of providing new ideas to treat diabetic wounds.